2018
DOI: 10.1080/2162402x.2018.1524695
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of colitis arising from anti-PD-1 based therapy

Abstract: Colitis is a frequent, clinically-significant immune-related adverse event caused by anti-programmed death-1 (PD-1). The clinical features, timing, and management of colitis with anti-PD-1-based regimens are not wellcharacterized. Patients with advanced melanoma that received either anti-PD-1 monotherapy ("monotherapy") or combined with ipilimumab ("combination therapy") were screened from 8 academic medical centers, to identify those with clinically-relevant colitis (colitis requiring systemic steroids). Of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 29 publications
0
55
0
Order By: Relevance
“…12,13 Although there is not a clear relation between the type of checkpoint inhibitor and the induction of irAEs, some toxicities, such as hypophysitis and colitis, are found with a higher prevalence among patients receiving anti-CTLA-4 mAb agents, either as single agents or in combination with anti PD1/PDL1 inhibitors. 14,15 As described in the literature, diarrhea associated with anti-CTLA-4 therapy usually appears after 7-8 weeks from the first infusion, while anti-PD1 associated diarrhea usually onsets as late as 12-24 weeks following treatment initiation. 14,15 These diarrheas have been linked to macroscopic and microscopic alterations similar to the ones found on immune-mediated colitis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…12,13 Although there is not a clear relation between the type of checkpoint inhibitor and the induction of irAEs, some toxicities, such as hypophysitis and colitis, are found with a higher prevalence among patients receiving anti-CTLA-4 mAb agents, either as single agents or in combination with anti PD1/PDL1 inhibitors. 14,15 As described in the literature, diarrhea associated with anti-CTLA-4 therapy usually appears after 7-8 weeks from the first infusion, while anti-PD1 associated diarrhea usually onsets as late as 12-24 weeks following treatment initiation. 14,15 These diarrheas have been linked to macroscopic and microscopic alterations similar to the ones found on immune-mediated colitis.…”
Section: Introductionmentioning
confidence: 96%
“…14,15 As described in the literature, diarrhea associated with anti-CTLA-4 therapy usually appears after 7-8 weeks from the first infusion, while anti-PD1 associated diarrhea usually onsets as late as 12-24 weeks following treatment initiation. 14,15 These diarrheas have been linked to macroscopic and microscopic alterations similar to the ones found on immune-mediated colitis. 16 In general terms, drug-induced microscopic colitis (MC) can be grouped into two main categories, known as microscopic colitis: collagenous and lymphocytic colitis, both of which have a grossly normal endoscopic appearance and are differentiated by histology.…”
Section: Introductionmentioning
confidence: 96%
“…Notably, we observed a significant degree of heterogeneity between studies, which may be partly explained by differences in their inclusion criteria. For example, many studies included patients with any gastrointestinal symptom, 14,22,25,27,35,37,41,[60][61][62] while others were more stringent and only included patients exhibiting at least CTCAE grade 2 40,63,64 or 3 23,34 diarrhoea, endoscopic and/or histological evidence of inflammation, 16,33,42,44,[65][66][67] patients requiring corticosteroids 24,30 or having some response to immunosuppressive therapy. 68 Moreover, there was marked variation between studies Finally, in the subgroup analysis we included some studies where not all the study group belonged to the covariate being analysed.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a retrospective analysis, and so it could be argued that patients requiring corticosteroids at baseline might have had an increased burden of comorbidity and reduced performance status as a potentially important confounding issue for survival. In addition to their potential impact on checkpoint inhibitor efficacy, it is also important to consider other potential side effects of immunosuppressive therapy in cancer patients treated with checkpoint inhibitors.Five studies reported safety outcomes in corticosteroid monotherapy, including no 'major adverse events' in 16 corticosteroid-treated patients,40 corticosteroid-induced diabetes mellitus in a cohort of 12 treated patients,60 adrenal insufficiency (n = 5), hyperglycaemia (n = 4), musculoskeletal issues (n = 3), volume overload (n = 2), hypertension, psychosis, insomnia and clostridium difficile colitis of 109 treated patients,23 hyperglycaemia, labile mood and vaginal candidiasis,40 and one study reporting infectious colitis in 2 patients alongside the other commonly documented corticosteroid complications in 23 corticosteroid-treated patients 30.…”
mentioning
confidence: 99%
“…Anti‐CTLA‐4 antibody‐related gastrointestinal irAEs can occur throughout the treatment course, and can develop even more than 1 month after the completion of therapy . The median time of onset is 6.14 weeks (range 3.71‐8.14 weeks), whereas resolution time is 6.86 weeks (range 4.14‐8.43 weeks), compared to resolution time 25.4 weeks of anti‐PD‐1 . Combination therapy of anti‐CTLA‐4 and anti‐PD‐1 predictably leads to an earlier development of gastrointestinal toxicity (7.2 vs 25.4 weeks, P < .0001) compared to anti‐PD‐1 monotherapy …”
Section: Gastrointestinal Iraesmentioning
confidence: 99%